Genetic diversity analyses of Mycosphaerella eumusae causing Septoria leaf spot disease of banana in India - R. THANGAVELU*, P. GANGA DEVI and (Indian Phytopathology, 2014)
The leaf spot diseases caused by Mycosphaerella spp. are considered as one of the major constraints of banana production in entire banana growing regions of India. To identify the major leaf spot pathogen, a total of 99 isolates of leaf spot pathogen were isolated from different banana growing states. All these isolates were identified as M. eumusae based on cultural and morphological characters of the fungus. For confirmation, the rDNA-ITS region of all the 99 isolates of M. eumusae was sequenced and the Blast analysis showed 99-100% similarity only with M. eumusae, which causes Septoria leaf disease in banana. Further, the genetic diversity analyses carried out using the sequence data of rDNA-ITS region and by RAPD indicated the presence of 8-12 haplotypes among the M. eumusae isolates and also the existence of 98-100% homology between the three species of Mycosphaerella (M. musicola, M. fijiensis and M. eumusae) which are the major leaf spot disease causing pathogens in different banana growing regions of the world. This suggests that all these three species of Mycosphaerella have been derived from a common ancestor. The phylogenetic analysis also indicated that both these molecular methods have also clearly distinguished all the three species of Mycosphaerella by grouping them separately but in the major sub cluster of either M. musicola or M. fijiensis. This paper reports for the first time, the genetic diversity analysis carried out among the wide population of M. eumusae isolates that are causing severe yield and quality loss to banana in India.